2018
DOI: 10.1111/nmo.13368
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glial cell activation protects enteric neurons from damage due to diabetes in part via the promotion of neurotrophic factor release

Abstract: Enteric glial cell activation can protect enteric neurons from damage due to diabetes in the acute stage of the disease, in part via the promotion of neurotrophin release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…One of the earliest articles to report the protective role of GDNF on enteric neuropathy was a study by Anitha et al Using both in vitro culture system of enteric neurons as well as an in vivo streptozotocin‐induced diabetic mouse model, Anitha et al demonstrated that hyperglycemia induced neuronal apoptosis and loss of nitrergic inhibitory neurons in the ENS, and GDNF overexpression in transgenic mice prevented hyperglycemia‐induced changes in the ENS . Interestingly, in the current issue, Luo et al demonstrated that GDNF levels, along with NGF and NT‐3, increased in varying degrees in the gut during the acute stage of diabetes before loss of enteric neurons occurs . Expression of GDNF was significantly decreased in the colon of diabetic rats eight and twelve weeks after disease onset, which was coincident with the loss of enteric neurons, specifically the nitrergic inhibitory neurons and cholinergic excitatory neurons .…”
Section: Role Of Neurotrophic Factors In Neuroprotection and Neuroplamentioning
confidence: 87%
See 2 more Smart Citations
“…One of the earliest articles to report the protective role of GDNF on enteric neuropathy was a study by Anitha et al Using both in vitro culture system of enteric neurons as well as an in vivo streptozotocin‐induced diabetic mouse model, Anitha et al demonstrated that hyperglycemia induced neuronal apoptosis and loss of nitrergic inhibitory neurons in the ENS, and GDNF overexpression in transgenic mice prevented hyperglycemia‐induced changes in the ENS . Interestingly, in the current issue, Luo et al demonstrated that GDNF levels, along with NGF and NT‐3, increased in varying degrees in the gut during the acute stage of diabetes before loss of enteric neurons occurs . Expression of GDNF was significantly decreased in the colon of diabetic rats eight and twelve weeks after disease onset, which was coincident with the loss of enteric neurons, specifically the nitrergic inhibitory neurons and cholinergic excitatory neurons .…”
Section: Role Of Neurotrophic Factors In Neuroprotection and Neuroplamentioning
confidence: 87%
“…BDNF expression in the Caco-2 cell culture is increased following IBS-D fecal supernatant treatment 3,26,31 GDNF Rat Ileum Enteric glial cells Ischemia reperfusion upregulates GDNF expression by the enteric glial cells in the rat ileum, which helps to maintain intestinal barrier function. GDNF level is elevated in the rat ileum during the early stage of diabetes, which protects enteric neurons from hyperglycemia-induced cellular damage 38,41 Human Ileum Enteric glial cells and enterocytes, HT29B6 and Caco-2 cell lines GDNF activates the Ret/GFRα receptor complex and contributes to epithelial barrier stabilization 5 NGF Rat Jejunum, ileum, and colon Epithelial cells, mast cells, smooth muscle cells, enteric neurons and glial cells Many factors can increase NGF expression and release in the gut, including but not limited to: gut infection, gut inflammation, mechanical distension of the gut wall, neonatal maternal separation, diabetes 6,10,12,[14][15][16]35,41 Human Colon Immune cells in the lamina propria NGF expression is elevated in the colonic mucosa from IBS patients, which may contribute to visceral hypersensitivity and impaired gut barrier function in these patients 17,18 NT−3…”
Section: Neurotrophi C Fac Tor S and Viscer Al S Ens Itivit Ymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that EGCs begin to proliferate in the ileum of diabetic mice 4 weeks after the model establishment. The number of EGCs decreased after 8 weeks compared with 4 weeks [28]. However, few articles clearly reveal the mechanism of EGC apoptosis induced by hyperglycemia.…”
Section: Discussionmentioning
confidence: 97%
“…The original glucose concentration of the DMEM medium to cultivate EGCs is 25 mM (mmol L -1 ). We used D-(+) -Glucose (Sigma, St. Louis, MO, USA) to modulate hyperglycemia concentration and D-(+) -Mannitol (Sangon Biotech, Shanghai, China) to modulate hypertonic concentration [27,28].…”
Section: Methodsmentioning
confidence: 99%